2017
DOI: 10.3390/ma10080883
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Tensile and Creep Properties of Ta20Nb20Hf20Zr20Ti20 High Entropy Alloy

Abstract: This paper examines the microstructure and mechanical properties of Ta20Nb20Hf20Zr20Ti20. Two casting processes, namely, gravity casting and suction-assisted casting, were applied, both followed by Hot Isostatic Pressing (HIP). The aim of the current study was to investigate the creep and tensile properties of the material, since the literature review revealed no data whatsoever regarding these properties. The main findings are that the HIP process is responsible for the appearance of a Hexagonal Close Packed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Although this substitution is useful for achieving the mentioned aims, it may result in a poor mixing of the raw constituents, which causes low homogeneity of the finally obtained material. Furthermore, since the conventional way of producing HEAs is vacuum arc melting [ 248 , 249 , 250 , 251 ], the main problem arises due to the difference in melting points and vapor pressures of the alloying elements at high temperatures. Additionally, oxidation resistance of the alloying refractory elements requires an extremely high operating vacuum, at which low-melting constituents usually evaporate.…”
Section: Modern and Future Trends In Additive Manufacturing Of Crmmentioning
confidence: 99%
“…Although this substitution is useful for achieving the mentioned aims, it may result in a poor mixing of the raw constituents, which causes low homogeneity of the finally obtained material. Furthermore, since the conventional way of producing HEAs is vacuum arc melting [ 248 , 249 , 250 , 251 ], the main problem arises due to the difference in melting points and vapor pressures of the alloying elements at high temperatures. Additionally, oxidation resistance of the alloying refractory elements requires an extremely high operating vacuum, at which low-melting constituents usually evaporate.…”
Section: Modern and Future Trends In Additive Manufacturing Of Crmmentioning
confidence: 99%
“…The current processing of synthesizing HEAs is a vacuum arc melting [103][104][105][106][107]. Throughout applying this method, a vacuum atmosphere is used while heating the alloying materials up to a temperature higher permitting their complete melting.…”
Section: High Entropy Alloysmentioning
confidence: 99%
“…The large number of alloying elements leads to the formation of disordered solid solutions that maximize the configurational entropy. The microscopic analyses performed on HEAs may indicate ordered or disordered solid solutions, nanoprecipitates, or amorphous phases [ 1 ]. Senkov et al [ 2 , 3 ] reported that the process of producing equiatomic TaNbHfZrTi alloy consisted of melting in a VAR furnace, followed by three remeltings of the material for a better homogenization.…”
Section: Introductionmentioning
confidence: 99%